SEJARAH DAN ARKEOLOGI MADURAÂ·BARAT ABAD XIV-XVIII: SEBUAH PENGENALAN TENTANG PENGUASANYA - Lucas Partanda Koestoro (BRIN, 1995)
One interesting aspect related to the archaeological remains on the island of Madura is the relationship of the characters behind them with the historical journey that colored them. By regulating the views on the existence of various